A new typology - re-imagining a civic building - Roland, Stephanie (School of Architecture, Planning and Geomatics, 2017)
My personal interest in cities and their layering of spaces and functions served as a starting point for this dissertation. Cities evolve over time, and the resultant networks of movement and public spaces are the filters through which most inhabitants experience the city they live in. By examining the Cape Town CBD and surrounds, it became apparent that these networks have become secondary to other commercial systems. Whilst Cape Town has some open public spaces of historic significance such as the Grand Parade and Greenmarket Square, the public space network has become fragmented and often overwhelmed by commercial interests which inevitably limit public access and use. Upon closer examination, it seems that economic concerns have shaped the city rather than a layering and balance between public and private, access and control. A discernible building typology can be found in the inner city, one which I have referred to as the tower block. The tower blocks have varying programmes but hold in common private ownership and controlled access, thereby limiting the connection to the city severely, and in most cases do not add anything of value to the public urban fabric. Instead, where the tower block access meets the movement and public space network of the city a hostile environment is created, where loiterers and security guards jostle for control. The inhabitants and users of the tower blocks step from the city into a controlled, sterile environment, and do not interact with the urban environment further. Most of these tower blocks naturally accommodate office space in the CBD. Whilst it is not realistic to lay the onus on private investors and developers putting up tall buildings in the city to contribute extensively to the public urban space, civic buildings should shoulder that responsibility. Historically, as with the Old Town Hall overlooking the Grand Parade, this is how the public space network was constructed. Civic building and the publicly accessible space which they created were the generative elements of cities. By examining the CBD it became clear that the last extensive civic building done by the city was during the apartheid era, buildings such as the Civic Centre and Customs House on the foreshore. Built to deal with the growing administrative apparatus of that era, and following modernist guidelines the public spaces created by these buildings are mostly unused, due to unsuitable location and being awkwardly scaled and imposing. The trend for the city to instead lease tower blocks of generic office space to accommodate their civic functions has further led to a deterioration of the public urban realm, as a building typology focused on disconnection from the city now has to accommodate a constant influx of people whilst still having to maintain security for its internal workings. The street, entrances and internal corridors become crowded with people which they were not designed to contain, leading to a frustrating experience for both public and public servant alike. The focus of this thesis became to challenge the conventional tower block that makes up much of our cities today, by putting forward spatial possibilities that are flexible for alternate uses and new crossprogrammatic possibilities for a partnership between private building and public building. The connection between the private and public was made through the programme of an office building, which in its generic form has already become a typology that houses both public (civic) and private.